Associations between Adiponectin Gene Variability, Pro-inflammatory and Angiogenetic Markers: Implications for Microvascular Disease Development in Type 2 Diabetes Mellitus? - Kollia, Christina; Antonopoulos, Alexios S.; Siasos, Gerasimos; Konsola, Theodosia; Oikonomou, Evangelos; Gouliopoulos, Nikolaos; Tsigkou, Vasiliki; Papapanagiotou, Aggeliki; Kassi, Eva; Tentolouris, Nicholas; Katsiki, Niki; Vavuranakis, Manolis; et al. (Current Vascular Pharmacology, 2019)
Background: Adiponectin gene (ADIPOQ) variability may affect the risk for type 2 diabetes mellitus (T2DM) but it remains unclear whether it is involved in microvascular complications. Objective: To explore the impact of ADIPOQ variability on markers of inflammation and angiogenesis in T2DM. Methods: Overall, 220 consecutive T2DM patients from our outpatient diabetic clinic were genotyped for G276T (rs1501299) and T45G (rs2241766) single nucleotide polymorphisms of ADIPOQ gene. Serum levels of interleukin-6 (IL-6), intercellular adhesion molecule-1 (ICAM-1), vascular endothelial growth factor (VEGF) were measured by enzyme-linked immunosorbent assay and high sensitivity Creactive protein (hsCRP) by immunonephelometry. Results: Homozygosity for the G allele on rs2241766 was associated with significantly lower serum VEGF and ICAM-1 levels compared with other genotype groups, but had no effect on IL-6. Genetic variability on rs1501299 was not associated with either VEGF or ICAM-1 levels, but T homozygotes for rs1501299 had significantly lower IL-6 concentrations compared with G carriers. Furthermore, the presence of the G allele on rs2241766 was associated with significantly lower HbA1c, whereas no associations were observed for both body mass index and hsCRP with either rs2241766 or rs1501299. Conclusion: Genetic variability on adiponectin gene was associated with serum levels of inflammatory and angiogenetic markers. Further research is required to elucidate the role of adiponectin in the development and/or progression of microvascular disease in T2DM patients.
Keywords: angiogenesis